IMPLEMENTASI DAKWAH ENTREPRENEUR DI PONDOK PESANTREN ASSALAFIY FATHUL ULUM JOMBANG - Elza Rohmayani; Suhari Suhari (JOURNAL SAINS STUDENT RESEARCH, 2025)
Assalafiy Fathul Ulum Jombang Islamic Boarding School is one of the Islamic boarding schools located in Jombang Regency, East Java, which is strong in teaching Islam, not only providing religious knowledge, but also equipping students with entrepreneurial skills so that they can be economically independent and contribute positively to society. There are two problems studied in this thesis, namely: (1) How is the Implementation of Entrepreneurial Da'wah at Assalafiy Fathul Ulum Jombang Islamic Boarding School? and (2) How is the Role of Caregivers in Forming an Entrepreneurial Spirit in students at Assalafiy Fathul Ulum Jombang Islamic Boarding School? To answer these two problems, this researcher uses a qualitative approach with primary data types obtained through observation, interviews, and documentation, as well as secondary data from various sources such as books, articles, journals, and related literature. The subjects of this study consisted of Kyai Ahmad Habibul Amin (caretaker of the Assalafiy Fathul Ulum Islamic Boarding School in Jombang), Ustadz of the Assalafiy Fathul Ulum Islamic Boarding School in Jombang, Chairman of BUMP (Islamic Boarding School-Owned Enterprises), and students who are members of the preneur. The results of this study indicate that the implementation of entrepreneurial da'wah at the Assalafiy Fathul Ulum Islamic Boarding School aims to develop an entrepreneurial spirit among students as part of their provision to have financial independence and make a positive contribution to society. This da'wah does not only focus on religious teachings, but also involves practical skills that support the economic independence of students after they leave the Islamic boarding school, and this da'wah does not only focus on religious teachings, but also involves practical skills that support the economic independence of students after they leave the Islamic boarding school. This study is expected to make a significant contribution to the development of religious moderation in Indonesia.